2008
DOI: 10.4049/jimmunol.181.11.7936
|View full text |Cite
|
Sign up to set email alerts
|

Multimerization of Surfactant Protein D, but Not Its Collagen Domain, Is Required for Antiviral and Opsonic Activities Related to Influenza Virus

Abstract: Surfactant protein D (SP-D) plays important roles in the initial innate defense against influenza A virus (IAV). The collagen domain of SP-D is probably critical for its homeostatic functions in vivo and has been implicated in the modulation of macrophage responses to SP-D-ligand complexes. For the current studies, we used a panel of rat SP-D mutants lacking all or part of the collagen domain to more specifically evaluate the contributions of this domain to viral interactions. SP-D multimers lacking the collag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 44 publications
4
40
0
Order By: Relevance
“…For all strains, however, it was clearly demonstrated that RpNCRD exhibits HA inhibitory activity, in contrast to RhNCRD for which no activity could be measured in this assay. Dodecameric oligomerization thus appeared to be essential for native hSP-D to express its HA inhibitory activity, as determined previously (57,58), driven primarily by the aggregation properties of the fully assembled hSP-D molecule.…”
Section: Discussionsupporting
confidence: 60%
“…For all strains, however, it was clearly demonstrated that RpNCRD exhibits HA inhibitory activity, in contrast to RhNCRD for which no activity could be measured in this assay. Dodecameric oligomerization thus appeared to be essential for native hSP-D to express its HA inhibitory activity, as determined previously (57,58), driven primarily by the aggregation properties of the fully assembled hSP-D molecule.…”
Section: Discussionsupporting
confidence: 60%
“…Our results convincingly show, however, that trimeric collectin hSP-D-NCRDs can also act as opsonins to enhance neutrophil or monocyte/macrophage uptake of IAV. We have recently shown that small dodecamers of SP-D lacking the collagen domain but retaining the NH 2 terminus and hSP-D-NCRD trimers cross-linked with MAbs also promote neutrophil uptake of IAV (32,34). Hence, using several methods, we have shown that the collagen domain per se in not required for antiviral or opsonizing activity.…”
Section: Discussionmentioning
confidence: 93%
“…The capacity of SP-D to aggregate IAV is dependent on higher order multimeric structure, and trimeric NCRDs are devoid of aggregating activity (35). However, we recently observed that trimeric NCRDs with the R343V substitution can efficiently aggregate Phil82 but not SP-D resistant strains (27,36).…”
Section: D325a Shows Enhanced Interactions With Iav In Vitro-mentioning
confidence: 98%